ANALISIS FAKTOR PREFERENSI IMPLEMENTASI AKAD MUSYARAKAH MUTANAQISHAH DIBANDINGKAN AKAD IJARAH MUNTAHIYA BITTAMLIK PADA BANK JATIM SYARIAH SURABAYA - Ade Rahmawati; Irham Zaki (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The development of Islamic finance currently reaching a high stage by creating a varied and innovative financial product. One such product development is the musyarakah mutanaqishah and ijarah muntahiya bittamlik contracts, where the two contracts are attractive and have similiar mechanisms. Ijarah muntahiya bittamlik contract in Islamic finance more appear first than the contract musyarah mutanaqishah. But musyarakah mutanaqishah contract more widely used in the current sharia banking, ijarah muntahiya bittamlik contract more can be found in leasing and purchasing companies. The paper analyzes the application of musyarakah mutanaqishah contract on syariah banking and the reason sharia Jatim Bank prefer to apply the contract musyarakah mutanaqishah from ijarah muntahiya bittalmik contract. Then this paper also presents the advantages musyarakah mutanaqishah contract and lack of ijarah muntahiya bittamlik contract, which in the end musyarakah mutanaqishah contract more widely applied to Islamic banks, in Surabaya particular. Data analysis of this paper using case study analysis method. Where it has the conclusion that Bank Jatim Syariah Surabaya in taking a decision to choose a contract that will be applied to see from the contribution of the contract in the sharia banking. Other than in the tendency to choose some contract, Bank Jatim Syariah Surabaya also pay attention contract which is considered fo fulfill market requirement and have easy mechanism, so that doesn’t complicate employees of Bank Jatim Syariah Surabaya.Keywords: Election Policy, Musyarakah Mutanaqisah, Ijarah Muntahiya Bittamlik, Bank Jatim Syariah SurabayaREFERENCESAscarya. 2015. Akad dan Produk Bank Syariah. Jakarta: RajaGrafindo PersadaDsnmui.or.id diakses pada 14 April 2018 pukul 21.41Erinda, Aisyah ., et. al.2016. Analisis Faktor-faktor Preferensi Pelanggan Dan Pengaruhnya Terhadap Keputusan Pembelian(Studi Terhadap Pelanggan McDonald’s di Indonesia dan Malaysia). Malang: Universitas BrawijayaHijrianto, Didik. 2010. Pelaksanaan Akad Pembiayaan Ijarah Muntahiya Bittamlik Pada Bank Muamalat Indonesia Cabang Mataram. Semarang: Universitas Diponegorohttps://tafsir.com diakses pada tanggal 10 Juni 20018 pukul 23.03Kotler, Philip. 2000. Manajemen Pemasaran. Edisi Milenium, Jakarta: PrehallindoMuchtar, Bustari., et. al. 2016. Bank dan Lembaga Keuangan Lain. Jakarta: KencanaMuhamad. 2016. Manajemen Pembiayaan Bank Syariah. Yogyakarta: UPP STIM YKPNMunawir, S. 1997. Analisis Laporan Keuangan. Yogyakarta: LibertyNaf’an. 2014. Pembiayaan Musyarakah dan Mudharabah. Yogyakarta: Graha IlmuSantoso, Hurun dan Anik. 2015. Analisis Pembiayaan Ijarah Pada Perbankan Syariah. Surakarta: STIE-AASUsman, Husaini. 2009. Manajemen Teori, Praktik, Dan Riset Pendidikan. Jakarta: Bumi AksaraWibowo, Edy dan Untung Hendi Widodo. 2005. Mengapa Memilih Bank Syariah?. Bogor : Ghalia Indonesiawww.ojk.go.id diakses pada tanggal 16 Februari 2018 pukul 12:25Yin, Robert K. 2008. Studi Kasus: Desain dan Metode. Jakarta: Rajagrafindo Persada